Comparison of visual field and pattern electroretinography parameters in pseudoexfoliation glaucoma patients - بلال سنان; سليمان يوسف; يوسف حبيب (Latakia University Journal -Medical Sciences Series, 2024)
Aim: To study the correlation between pattern electroretinography (PERG) and visual field (VF) in pseudoexfoliation glaucoma patients. Methods and Materials: Our study included 42 eyes (27 patients), 15 of them with bilateral PXG and 12 with unilateral PXG, to compare them with 42 control eyes. Each studied patient had PERG and VF tests done. Measured PERG parameters were amplitude and latency time of P50, N95 waves in addition to P50-N95 amplitude. VF parameters were MD and MS. Results: There was a significant difference in all PERG parameters (P50 amplitude: 0.68, 2.24, N95 amplitude: -1.42, -3.97, N95 time: 113.13, 98.12, P50-N95 amplitude: 2.11, 6.21 in patients and controls, respectively (p<0.001)), except P50 time (P=0.94), and visual field parameters difference were also significant (MS: 13.97, 24.1, MD: 11.85, 1.32 in patients and controls, respectively (p<0.001)). Correlation between PERG and VF parameters was also significant, particularly between N95 amplitude and MD Conclusion: PERG sensitivity was high in detecting glaucomatous injury in PXG patients, which encourages its usage in routine glaucoma diagnosis.